Income inequalities in the risk of potentially avoidable hospitalisation for chronic obstructive pulmonary disease: a population data linkage analysis - Quinn, Nicholas; Gupta, Neeru (International Journal of Population Data Science, 2020)
Introduction Hospitalizations for ambulatory care sensitive conditions, of which chronic obstructive pulmonary disease (COPD) is among the most common, represent an indirect measure of the healthcare system to manage chronic disease. Research has pointed to disparities in various COPD-related outcomes between persons of lower versus higher income; however, few studies have examined the influence of patients’ social context on potentially avoidable COPD admissions. Objective The research explores the use of linked population census and administrative health data to assess the influence of income inequalities on the risk of hospitalization and rehospitalization for COPD among Canadian adults. Methods This analysis utilizes data from the 2006 Census linked longitudinally to the 2006/07-2008/09 Discharge Abstract Database. Multiple logistic regressions were conducted to assess the independent influence of income inequality on the risks of hospitalization and of six-month rehospitalization due to COPD among the population aged 30-69, controlling for age, sex, education and other sociodemographic characteristics. Results Compared to adults in the most affluent income quintile, the adjusted odds of COPD hospitalization were significantly greater in the 4th highest income quintile (OR: 1.38; 95%CI: 1.30-1.47), and peaked for those in the least affluent quintile (OR: 2.92; 95%CI: 2.77-3.09). Among individuals who had been hospitalized at least once for COPD in the study period, and compared to the most affluent group, the adjusted odds of readmission were highest in the least affluent group (OR: 1.39; 95%CI: 1.22-1.58). Conclusions Despite Canada’s system of universal health coverage, a clear income gradient in the risk of being hospitalized and, to some extent, re-hospitalized for COPD, is found. Income inequalities fueling excess hospitalizations reinforce the importance of integrating social and economic issues in primary care to meet the ambulatory needs of this population.